Gender and gut microbiota composition determine hepatic bile acid, metabolic and inflammatory response to a single fast-food meal in healthy adults. Issue 5 (May 2021) - Figge, A.; Sydor, S.; Wenning, C.; Manka, P.; Assmuth, S.; Vilchez-Vargas, R.; Link, A.; Jähnert, A.; Brodesser, S.; Lucas, C.; Nevzorova, Y.A.; Faber, K.N.; et al.
Abstract: Background & aims: Regular consumption of fast-food (FF) as a form of typical Western style diet is associated with obesity and the metabolic syndrome, including its hepatic manifestation nonalcoholic fatty liver disease. Currently, it remains unclear how intermittent excess FF consumption may influence liver metabolism. The study aimed to characterize the effects of a single FF binge on hepatic steatosis, inflammation, bile acid (BA), glucose and lipid metabolism. Methods: Twenty-five healthy individuals received a FF meal and were asked to continue eating either for a two-hour period or until fully saturated. Serum levels of transaminases, fasting BA, lipid profile, glucose and cytokine levels as well as transient elastography and controlled attenuation parameter (CAP; to assess hepatic steatosis) were analyzed before (day 0) and the day after FF binge (day 1). Feces was collected prior and after the FF challenge for microbiota analysis. Results: The FF meal induced a modest increase in CAP, which was accompanied by a robust increase of fasting serum BA levels. Surprisingly, levels of cholesterol and bilirubin were significantly lower after the FF meal. Differentiating individuals with a relevant delta BA (>1 μmol/l) increase vs. individuals without (delta BA ≤1 μmol/l), identified several gut microbiota, as well as gender to be associated with the BA increase and the observed alterations in liver function, metabolism and inflammation. Conclusion: A single binge FF meal leads to a robust increase in serum BA levels and alterations in parameters of liver injury and metabolism, indicating a novel metabolic aspect of the gut–liver axis.